ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) KARYAWAN DI UNIT REKAM MEDIS RUMAH SAKIT SWASTA X - Sartika, Iik (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2019)
The hospital is one example of a labor intensive organization with all sorts of human resources therein. The hospital is also a health care institution that is the center of service for the community. One of the problems that seemed is the attitude of employees who reduce the quality of hospital services. Organizational Citizenship Behavior (OCB) 's activity in the medical record unit of private hospital X has not been going well. There are four employees who have low OCB levels and two employees have a high OCB level. The causal factor of OCB in private hospital X medical record service is role clarity, leadership, motivational drives, organizational commitment, organizational justice, and traits individual. The recommendations that can be applied to improve OCB in the medical record unit of private hospital X are as follows: 1) clarify the basic task and function of the employee (Role Clarity), 2) Role model of the leader (Leadership), 3) put the word motivation ( Motivational Drives), 4) Increase organizational commitment with appreciation from the Organization (Organizational Commitment), 5) Equal treatment of employees (Organizational Justice), 6) Development of self confidance, team building, and leadership Employees (Individual Traits).